COVID-19 and Labour Law: Latvia - Zane Rasnača (Italian Labour Law e-Journal, 2020)
The Latvian response to the COVID-19 crisis can be praised as successful since the pandemic reached its peak as early as 1 April and there has been a gradual decrease of new cases since then. Nonetheless, the consequences for the labour market are significant. Latvia adopted several measures, including a wage subsidy, income support for the self-employed, and tax relief for companies. However, some of these measures have been deemed ineffective and, in addition, there is evidence that circumvention of some labour laws is taking place in the shadow of the crisis.